2023
DOI: 10.34172/ijhpm.2023.8021
|View full text |Cite
|
Sign up to set email alerts
|

How the Stringency of the COVID-19 Restrictions Influences Motivation for Adherence and Well-Being: The Critical Role of Proportionality

Joachim Waterschoot,
Sofie Morbée,
Omer Van den Bergh
et al.

Abstract: Background: The stringency of the measures taken by governments to combat the COVID-19 pandemic varied considerably across countries and time. In the present study, we examined how the proportionality to the epidemiological situation is related to citizens’behavior, motivation and mental health. Methods: Across 421 days between March 2020 and March 2022, 273,722 Belgian participants (Mage = 49.47; 63.9% female; 33% single) completed an online questionnaire. Multiple linear mixed regression modeling was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The following study illustrates one contribution of our project. We examined how the proportionality of measures taken by public authorities between March 2020 and March 2022 to face the epidemiological situation was related to citizens' behaviour, motivation and mental health (Waterschoot, Morbée, Van den Bergh, et al, 2023). An important conclusion that we largely communicate was that stringent measures are not per se demotivating or damaging people's wellbeing, nor are lenient measures as such motivating or enhancing well-being.…”
Section: The Motivation Barometer (2020-2022)mentioning
confidence: 99%
“…The following study illustrates one contribution of our project. We examined how the proportionality of measures taken by public authorities between March 2020 and March 2022 to face the epidemiological situation was related to citizens' behaviour, motivation and mental health (Waterschoot, Morbée, Van den Bergh, et al, 2023). An important conclusion that we largely communicate was that stringent measures are not per se demotivating or damaging people's wellbeing, nor are lenient measures as such motivating or enhancing well-being.…”
Section: The Motivation Barometer (2020-2022)mentioning
confidence: 99%
“…Another long‐term investigation, spanning 421 days of the crisis between March 2020 and March 2022, showed that the effect of hospitalization load fully depends on the stringency of the implemented measures (Waterschoot, Morbée, Van den Bergh, Yzerbyt, et al., 2023). What especially appears critical is the proportionality between stringency and hospitalization load, with a balance between both required to generate positive or, alternatively, avoid negative effects on motivation, basic needs, and mental health.…”
Section: Part 2: Synthesis Of Key Findingsmentioning
confidence: 99%
“…As such, the Motivation Barometer helped politicians navigate the crisis using evidence‐informed/based recommendations rather than anecdotic and intuition‐driven arguments. The advice given to policymakers both dealt with the way of framing and explaining decisions (Pope et al., 2018) as well as with the type of decisions being made, as both can impact people's health concerns/risks and need satisfactions positioned in the middle of Figure 2 (Waterschoot, Morbée, Van den Bergh, Yzerbyt, et al., 2023). Illustrative examples are: allowing two close contacts for singles during Christmas gatherings in 2020 (Waterschoot, Morbée, Van den Bergh & Vansteenkiste, 2023) and rescheduling leisure time activities of youth such that both primary and secondary school students can participate in one single leisure time activity during an extended school lockdown instead of primary school students participate in an unlimited number and secondary school students being prohibited to engage in any leisure time activity.…”
Section: Part 3: Societal Role Of the Motivation Barometermentioning
confidence: 99%